Effectiveness of Topical Garlic Extract (Allium sativum) Cream on Wound Healing in Mice with Acute Injury Model Case Review of Vascular Endothelial Growth Factor Cytokine Expression - Zaenal; Baso Witman Adiaksa; St. Aminah Ali; Wahyudi Muchsin; Jukarnain; Rini Mustamin (Postgraduate, University of Mataram, 2023)
Wounds will cause problems if the handling is not good, causing chronic wounds. Garlic (Allium Sativum) is a typical tropical plant including Indonesia, whose tubers are often used in traditional medicine, including to heal wounds. (VEGF) as a Predictor of Wound Healing) in the rat model of acute injury. Experimental research was carried out using the Randomized Post Test Control Group design. This research was conducted using 4 laboratories, namely the Biopharmaca Research Activity Center (PKP) of Hasanuddin University for the process of making Garlic Extract Topical Cream (EBP), Animal Laboratory, Faculty of Medicine, Hasanuddin University for the maintenance and treatment of experimental animals. , Laboratory of Histopathology Maros Veterinary Center for making Histopathology slides, using 54 Wistar strain Rattus novergicus rats by making excisions on the left and right backs with a diameter of 8 mm using a punc byopsia. Then the rats were divided into 3 groups, namely the negative control group of 0.9% NaCl, the positive control group of 3% oxytetracycline and the treatment group of 10% topical garlic extract cream. The wound tissue of each group was observed microscopically on days 3, 7 and 14. The results showed that wound healing using topical garlic extract cream (Allium sativum) was better than the control group by increasing the expression of Vascular Endothelial Growth Factor (VEGF).